2015
DOI: 10.1292/jvms.14-0316
|View full text |Cite
|
Sign up to set email alerts
|

The influences of hyperbaric oxygen therapy with a lower pressure and oxygen concentration than previous methods on physiological mechanisms in dogs

Abstract: Recently, hyperbaric oxygen therapy with a lower pressure and oxygen concentration (L-HBOT) than previous methods has been used for dogs in Japan; however, the influences of L-HBOT on dogs have not been clarified. To verify the influences of L-HBOT on physiological mechanism in dogs, we investigated blood gas parameters, glutathione peroxidase (GPx) activity, heart rate variability, stress-related hormones and skin conductance (SC) in 4 clinically normal beagle dogs with catheters in their carotid arteries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Species and number of colony‐forming units (CFU) were recorded for each culture. A bacterial load score (BLS) was identified and assigned for each cultured bacteria as previously described: 0 = no growth or isolated from broth culture only, 1 = <50 CFU, 2 = 50‐100 CFU, and 3 = >100 CFU …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Species and number of colony‐forming units (CFU) were recorded for each culture. A bacterial load score (BLS) was identified and assigned for each cultured bacteria as previously described: 0 = no growth or isolated from broth culture only, 1 = <50 CFU, 2 = 50‐100 CFU, and 3 = >100 CFU …”
Section: Methodsmentioning
confidence: 99%
“…These previously reported indications have provided only subjective evidence of benefit from HBOT in dogs, with no comparison or controlled group investigation . Investigative evidence regarding the efficacy of this therapy for any type of wound healing in dogs is lacking; however, recent data have been published on its safety and physiologic effects of improved tissue and arterial and transcutaneous oxygenation . Currently, use of HBOT as an adjunct to any wound healing in dogs is based on subjective or anecdotal evidence evaluating complicated wounds in dogs, and research studies evaluating complicated wounds in rabbits, rats, and man .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor erythroid 2-related factor 2 (NRF2) is believed to play a crucial role in MHOT's cellular defense mechanism against oxidative stress. 55 It is suggested that MHOT interventions may aid in the removal of free radicals, thereby preventing potential apoptotic pathways triggered by oxygen-derived free radicals and therefore, exerting a protective effect. Typically administered daily for 1 to 2 h at pressures ranging from 2.0 to 2.8 ATA, HBOT is commonly utilized over 3 to 10 sessions for sports-related injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been demonstrated that 30 min after HBOT with 30% oxygen pressure at 1.3 ATA in dogs, GPx activity in erythrocytes increased. The nuclear factor erythroid 2-related factor 2 (Nrf2), a redox-sensitive transcription factor, is thought to play a key role in the cellular defense against oxidative stress by upregulating the transcription of antioxidant stress proteins like GPx and phase II defense enzymes [ 28 ]. Additionally, in the liver tissues of STZ-induced diabetic rats, oxidative-stress-related changes in the mRNA and protein expression of antioxidant enzymes, such as copper-zinc superoxide dismutase (Cu-Zn SOD) and catalase (CAT), have been found [ 29 ].…”
Section: Discussionmentioning
confidence: 99%